Can light absorption of black carbon still be enhanced by mixing with absorbing materials?. (15th May 2021) - Feng, Xue; Wang, Jiandong; Teng, Shiwen; Xu, Xiaofeng; Zhu, Bin; Wang, Jiaping; Zhu, Xijuan; Yurkin, Maxim A.; Liu, Chao
Abstract: Strongly absorbing black carbon (BC) particles are commonly mixed with other aerosols in the ambient atmospheres, resulting in absorption enhancement known as the lensing effect. If other absorbing aerosols such as mineral dust and brown carbons (BrCs) are mixed with BC particles, resulting absorption properties are still less certain. Such mixtures are common due to large amounts of BrC (and tarballs) co-emitted with BC from biomass burning. Thus, this study focuses on mixtures of two absorbing carbonaceous aerosols with different spectral variations of absorption, and reveals the influences of mixing states on their absorption, especially on their spectral variation and enhancement. Three typical mixing states (internally, partially and externally mixed) and complex nonspherical BC structures (fractal aggregates) are considered accurately in the light scattering simulations. The absorption Angstrom exponent (AAE) of internally mixed particles can increase to over 2 when BrC volume fraction is above 70%, but it is systematically smaller (by up to 0.1) than those of the partially mixed and externally mixed particles. Different from non-absorbing coating acting as a lens, internal mixing of BC and BrC may not enhance BC absorption at shorter wavelengths, while the total absorption may even be reduced due to the "protection" of BC by the BrC coating, referred to as a "shielding effect". Specifically, absorption enhancement in the case of internal mixing is sensitive to coating absorptivity (influenced by both its refractive index and volume fraction), and becomes close to or even smaller than 1 as the coating becomes more absorbing. Furthermore, the mixing states of two absorbing aerosols would surely affect absorption attribution as well as downstream estimations of BC heating effects. Thus, it should be carefully considered in future studies. Graphical abstract: Image 1 Highlights: Partially mixed BC and BrC result in similar optical properties to external mixing, but different from the internal mixing. Internal BC-BrC mixing would not enhance absorption at short wavelength due to stronger shielding effect over lensing effect. Smaller aerosol AAE values would be obtained if BC and BrC are well internally mixed. BC and BrC mixing states would significantly affect their attribution.